Combination of vinorelbine + doxorubicin in advanced breast cancer. - Lorvidhaya V. (2014)
OBJECTIVE: To assess the efficacy of a vinorelbine + doxorubicin combination in terms of response rate and time to progression in patients with locally advanced or metastatic breast cancer. METHODS: Vinorelbine (25 mg/m2) and doxorubicin (25 mg/m2) were administered intravenously in a rapid injection on days 1 and 8 every 21 days. Initially, 3 courses of vinorelbine + doxorubicin were given. Patients with responding or stable disease received 6 more courses to a maximum of 9 courses. RESULT: Twenty-nine patients were entered into the study and 27 eligible patients were considered evaluable for response. Median age was 45 years (range 33 to 63). Overall response rate was 66.67% (18/27) (CR = 5, PR = 13). Median time to progression was 7.8 months (range 4 to 16) and the median survival time was 25.9 months. Median follow-up time was 8.5 months (range 1.5 to 25). Toxicity was generally moderate. Hematologic complication was the dose limiting toxicity. WHO grade III/IV neutropenia was observed in 18.5%/3.7% of patients. The major non-hematologic toxicities were nausea and phlebitis. Grade III nausea/vomiting was observed in 7.4% and grade III/IV phlebitis in 3.7%/3.7% of patients. No toxic deaths were observed. CONCLUSION: The present vinorelbine + doxorubicin combination was highly effective and generally well tolerated in cases of advanced breast cancer. Further studies are required.